Intergenerational engagement with Asian residents in long-term care facilities: a mixed method systematic review - Hao Liu; Anne Topping; Anne Topping; Ping Guo (Frontiers Media S.A., 2024)
IntroductionAsian countries are experiencing a rapid rise in their aging populations. Cognitive and physical decline associated with aging can limit social interaction. This particularly impacts on those residing in long-term care facilities and engagement with children and young people. Intergenerational engagement has known benefits on the health and wellbeing of older people, it is unclear what the impact of intergeneration engagement interventions might have on older people in Asian long-term care settings. This review aims to evaluate the effectiveness and experiences of intergenerational engagement with older people in long-term care facilities in Asia.MethodsTen databases were searched to locate empirical studies of any design published in English or Chinese from January 2000 to June 2023. The search was limited to papers reporting effectiveness and/or experiences of intergenerational engagement on older people residing in Asian long-term care settings. The protocol was registered with PROSPERO (CRD42023413935) and followed PRISMA guidelines for reporting. A convergent design employing narrative synthesis was used to synthesize and integrate findings.ResultsFrom initial searches, 1,092 records were identified, of which 13 studies were retained for the review: 7 quantitative (including 1 randomized controlled trial, 1 cross-sectional observational design, and 5 quasi-experimental designs), 3 qualitative, and 3 mixed methods. Included studies were of variable quality. Quantitative evidence revealed that intergenerational engagement reduced depression (4.47 vs. 8.67, p = 0.005), negative emotions (14.11 vs. 16.56, p = 0.030), and feelings of loneliness (p < 0.01) among older people; and increased quality of life (mean change = −1.91; 95% CI = −3.18, −0.64) and strengthens interpersonal interactions (p = 0.025). Qualitative insights suggested that intergenerational engagement could foster emotional bonds, enhance intergenerational relationships, promote lifelong learning, satisfy social needs and improve older peoples' overall quality of life. However, some challenges such as language differences and noise levels can hinder successful implementation of intergenerational engagement.ConclusionThis review indicates that intergenerational engagement can reduce depression and loneliness, improve quality of life, and strengthen social bonds for older individuals in Asian long-term care facilities. Despite some challenges, the evidence underlines its potential to meet the emotional and social needs of older people. Recognizing and addressing delivery challenges is essential for effective implementation.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023413935, identifier: CRD42023413935.